Usage of mobile phones among victims during the 2014 flood in Malaysia - A.Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha; Wok, Saodah; Ismail, Rizalawati (2016)
One of the worst ever flood disaster in the Malaysian history that occurred in December 2014 has caused a lot of damages including lives, houses and material possessions. Large parts of the country mainly the East Coast areas consisting of Kelantan, Terengganu and Pahang have badly affected. This study was conducted to explore the use of mobile phone during the 2014 Malaysian flood. A cross-sectional survey with a total number of 507 respondents who live in the flood affected areas was conducted to examine the use and satisfactions obtained from the usage of mobile phone. Being active users of mobile phone, flood victims mainly used mobile phones to obtain information about flood status in their house areas and to communicate with close family members. Furthermore, mobile phones were used to gratify social, entertainment, and mobility needs. Findings of the study will have implications on uses and gratifications, mobile phone use and natural disasters.